Предмет: Математика, автор: deed91

Решите всё то что есть на картинке

Приложения:

Ответы

Автор ответа: Moramora
1
  1. a)

 \frac{15 {x}^{2} }{6x + 15 {x}^{2} }  =  \frac{15 {x}^{2} }{3x(2 + 5x)}  =  \frac{5x}{2 + 5}

б)

 \frac{9x + 9y}{36 {x}^{2} - 36 {y}^{2}  }  =  \frac{9(x + y)}{36(x - y)(x + y)}  =  \frac{1}{4x - 4y}

2. 1)

 \frac{5}{12a - 12b}  -  \frac{3}{16a - 16b}  =  \frac{5}{12(a - b)}  -  \frac{3}{16(a - b)}  =  \frac{20 - 9}{48(a - b)}  =  \frac{11}{48(a - b)}

2)

 \frac{5x - 7}{ {x}^{2} - 4 }  +  \frac{3x - 2}{x - 2}  =  \frac{5x - 7}{(x - 2)(x + 2)}  +  \frac{3x - 2}{x - 2}  =  \frac{5x - 7 + (3x - 2)(x + 2)}{ {x}^{2} - 4 }  =  \frac{5x - 7 + 3 {x}^{2} + 4x - 4 }{ {x}^{2} - 4}  =  \frac{3 {x}^{2} + 9x - 11 }{{x}^{2} - 4 }

3.

 \frac{3x - 9 {x}^{2}  }{ {x}^{2} + 6x + 9 }  \div  \frac{1 - 9 {x}^{2} }{ {x}^{2} - 9 }  =   \frac{3x(1 - 3x)}{ {x + 3}^{2} }  \times  \frac{(x - 3)(x + 3)}{(1 - 3x)(1 + 3x)}  =  \frac{3x(x - 3)}{(x + 3)(1 + 3x)}

х=1

 \frac{3(1 - 3)}{(1 + 3)(1 + 3)}  =  \frac{3( - 2)}{ {4}^{2} }  =  -  \frac{6}{16}  =  -  \frac{3}{8}

4.

 \frac{z}{t}  \times  \frac{t}{k}  =  \frac{z}{k}  \\  \frac{z}{k}  = 5 \times 12 = 60

Похожие вопросы